Characterization of hydrogenated graphite powder by X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry. Issue 84 (26th August 2016) - Xie, Wenjing; Ng, Kai Mo; Weng, Lu-Tao; Chan, Chi-Ming
Abstract : Hydrogenated graphite powder was obtained through Birch reduction of graphite powder and characterized by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) at 500 °C. Abstract : Hydrogenated graphite powder was obtained through Birch reduction of graphite powder and characterized by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) at 500 °C. The sp 3 carbons formed at the edges of the surface of the hydrogenated graphite powder exhibited an sp 3 carbon peak in the XPS C1s spectrum. The sp 3 -to-sp 2 carbon ratio calculated from the XPS spectra increased from 0.08 to 1.19 after hydrogenation. Two sets of peaks, the C x − and C x H − ion series (where x = 1, 2, 3…), were identified in the ToF-SIMS spectra of both the graphite powder and hydrogenated graphite powder. The difference between these two spectra represented an increase in the normalized intensities of the H − and C x H − ions in the spectrum of the hydrogenated graphite powder, indicating the formation of more sp 3 carbons on the surface.